Impurity Profiling: A Review - B, Bhagwat Ashlesha; M, Khedkar K. (Asian Journal of Pharmaceutical Research and Development, 2022)
Impurities are any substances, such as starting materials or intermediates, that coexist with the parent drug or arise from side reactions. Interest in impurities present in APIs continues to grow. Nowadays, not only purity profile but also impurity profile is mandated by various regulatory agencies. Impurity profiling is a generic name for a group of analytical working groups such as describing, quantifying and characterizing identified and unidentified impurities present in a new drug substance. Impurity profiling is a novel approach aimed at detecting, identifying, structuring and quantifying organic and inorganic impurities and residual solvents in pharmaceuticals. Various regulatory bodies, such as ICH, USFDA, UKMHRA, and India’s CDSCO, focus on impurity profiling and have formulated guidelines for impurity management and restriction. Impurities are classified into different categories based on their origin, type of composition, and biological safety. The presence of these unwanted chemicals or substances may affect the safety and effectiveness of the final medicinal product. This review focuses on the sources of impurities, their classification, and various analytical methods for the identification and quantification of impurities. Terms such as residual solvent, by-product, transformation product, decomposition product, reaction product, and related products are often used to define impurities.